Compendium of the economically important seashells in Panay, Philippines - Laureta, Liberato V. (University of the Philippines Press, 2008)
With more than three hundred photographs in full color, the book is a vivid and informative encyclopedia of seashells in the natural world. The unique combination of photographs and the comprehensive and concise accounts of the different species make this book a valuable reference material. It is undoubtedly a welcome addition to the limited literature available in the field of seashell taxonomy and ecology in the Philippines. It can serve not only as an introductory book for students in marine biology, fisheries, aquatic fauna, or related areas but also as a guide for researchers working on different marine habitats of the Philippine coastal areas.